2005
DOI: 10.1007/s11167-005-0566-7
|View full text |Cite
|
Sign up to set email alerts
|

Porous Structure of Activated Carbon Fibers

Abstract: The dependence of the microporous structure of activated carbon fibers on the carbonization temperature of hydrate-cellulose fibers was studied by BET, TVFMP, and Horvath and Kawazoe techniques and methods of the nonlocal density functional theory. The surface energy distribution function was obtained, together with the micropore size distribution curves. It was shown that the effective micropore sizes calculated by the TVFMP method are close to the maximum of the distribution function found in terms of the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Based on the shape of the adsorption isotherm, they provide direct information about the size distribution of pore volumes. Examples of such calculations for activated carbon adsorbents were given in [5][6][7][8] and showed that the NDFT method is quite informative.…”
mentioning
confidence: 99%
“…Based on the shape of the adsorption isotherm, they provide direct information about the size distribution of pore volumes. Examples of such calculations for activated carbon adsorbents were given in [5][6][7][8] and showed that the NDFT method is quite informative.…”
mentioning
confidence: 99%